Mechanically Activated Calcium Channel PIEZO1 Modulates Radiation-Induced Epithelial-Mesenchymal Transition by Forming a Positive Feedback With TGF-β1 - Huang, Jia-Qi; Zhang, Hao; Guo, Xue-Wei; Lu, Yan; Wang, Si-Nian; Cheng, Bo; Dong, Su-He; Lyu, Xiao-Li; Li, Feng-Sheng; Li, Yong-Wang (Frontiers in Molecular Biosciences, 2021)
TGF-β-centered epithelial-mesenchymal transition (EMT) is a key process involved in radiation-induced pulmonary injury (RIPI) and pulmonary fibrosis. PIEZO1, a mechanosensitive calcium channel, is expressed in myeloid cell and has been found to play an important role in bleomycin-induced pulmonary fibrosis. Whether PIEZO1 is related with radiation-induced EMT remains elusive. Herein, we found that PIEZO1 is functional in rat primary type II epithelial cells and RLE-6TN cells. After irradiation, PIEZO1 expression was increased in rat lung alveolar type II epithelial cells and RLE-6TN cell line, which was accompanied with EMT changes evidenced by increased TGF-β1, N-cadherin, Vimentin, Fibronectin, and α-SMA expression and decreased E-cadherin expression. Addition of exogenous TGF-β1 further enhanced these phenomena in vitro. Knockdown of PIEZO1 partly reverses radiation-induced EMT in vitro. Mechanistically, we found that activation of PIEZO1 could upregulate TGF-β1 expression and promote EMT through Ca2+/HIF-1α signaling. Knockdown of HIF-1α partly reverses enhanced TGF-β1 expression caused by radiation. Meanwhile, the expression of PIEZO1 was up-regulated after TGF-β1 co-culture, and the mechanism could be traced to the inhibition of transcription factor C/EBPβ expression by TGF-β1. Irradiation also caused a decrease in C/EBPβ expression in RLE-6TN cells. Dual luciferase reporter assay and chromatin immunoprecipitation assay (ChIP) confirmed that C/EBPβ represses PIEZO1 expression by binding to the PIEZO1 promoter. Furthermore, overexpression of C/EBPβ by using the synonymous mutation to C/EBPβ siRNA could reverse siRNA-induced upregulation of PIEZO1. In summary, our research suggests a critical role of PIEZO1 signaling in radiation-induced EMT by forming positive feedback with TGF-β1.